Penerapan Replikasi Data pada Aplikasi Ticketing Menggunakan Slony PostgreSQL - Defriyanuar Dhining; Yeni Rokhayati; Dwi Ely Kurniawan (Journal of Applied Informatics and Computing, 2017)
Nowadays, almost every company use web aplication to do their business activity. Besides multi-platform it also easier for installation and maintenance. Other that web application need a fast and reliable internet connection. It is necessity to make a server in local area network with syncronize database from one server to another server. Syncronize database will run using replication server database. Database replication can use many tool, one of them is Slony that is specially create for PostgreSQL. Replication database can also to pretend stopping application when there is bad internet connection. Replication database is one of stanby server tecknic because down server. Database synchronize will be buid using PHP programming language and PostgreSQL database with Slony which is open source at all, so it will reduce the cost of installation and maintenance.